Gender and leadership among the female students in a Malaysian public university - Hassan, Zaharah; Silong, Abu Daud; Abdul Aziz, Siti Fardaniah (2011)
The number of females elected to leadership positions is smaller as compared to males. This phenomenon happens not only among developing countries, but also in developed countries. Many reasons are identified as barriers such as the limited access to education for women. Lately, in Malaysia, the total number of female is more than male students in the higher education institutions, reaching to a proportion of 70:30. Does this means that the total number of female students elected as leaders has also increased? This article will explore the position of female students in student associations at one of the public university in Malaysia. Data is collected through document analysis, focused group interviews and in-depth interviews with relevant students involved in associations. The questions that need to be answered are: how many female students are directly involved with associations? What are their posts? What are the supporting and preventive factors, as well as the challenges they faced? The analysis shows that while many female students are elected as association representatives, the number who holds the post of President is disappointing. They also have to face similar challenges and obstacles as faced by women in the work setting. Based on the findings, a few recommendations are forwarded to assist students in improving their leadership skills.